TAK1 inhibition mitigates intracerebral hemorrhage-induced brain injury through reduction of oxidative stress and neuronal pyroptosis via the NRF2 signaling pathway - Zhao, Jing; Chen, Chunli; Ge, Lite; Jiang, Zheng; Hu, Zhiping; Yin, Lihong (Frontiers in Immunology, 2024)
Introduction Intracerebral hemorrhage (ICH) often triggers oxidative stress through reactive oxygen species (ROS). Transforming growth factor-β-activated kinase 1 (TAK1) plays a pivotal role in regulating oxidative stress and inflammation across various diseases. 5Z-7-Oxozeaenol (OZ), a specific inhibitor of TAK1, has exhibited therapeutic effects in various conditions. However, the impact of OZ following ICH and its underlying molecular mechanisms remain elusive. This study aimed to explore the possible role of OZ in ICH and its underlying mechanisms by inhibiting oxidative stress-mediated pyroptosis. Methods Adult male Sprague-Dawley rats were subjected to an ICH model, followed by treatment with OZ. Neurobehavioral function, blood-brain barrier integrity, neuronal pyroptosis, and oxidative stress markers were assessed using various techniques including behavioral tests, immunofluorescence staining, western blotting, transmission electron microscopy, and biochemical assays. Results Our study revealed that OZ administration significantly inhibited phosphorylated TAK1 expression post-ICH. Furthermore, TAK1 blockade by OZ attenuated blood-brain barrier (BBB) disruption, neuroinflammation, and oxidative damage while enhancing neurobehavioral function. Mechanistically, OZ administration markedly reduced ROS production and oxidative stress by facilitating nuclear factor-erythroid 2-related factor 2 (NRF2) nuclear translocation. This was accompanied by a subsequent suppression of the NOD-like receptor protein 3 (NLRP3) activation-mediated inflammatory cascade and neuronal pyroptosis. Discussion Our findings highlight that OZ alleviates brain injury and oxidative stress-mediated pyroptosis via the NRF2 pathway. Inhibition of TAK1 emerges as a promising approach for managing ICH.